Layanan Webform Terhadap Kepuasan Nasabah Dimoderasi Pengetahuan (Studi Pada Nasabah BSI di Kota Palembang) - Zulkarnain, Muhammad; Nurul Ilma Hasana Kunio; Marti Utari; Ahmad Ari Gunawan Sepriansyah; Ade Sukmawati (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2024)
This research aims to determine the effect of webform on customer satisfaction with knowledge as a moderating variable. The data analysis method uses quantitative with a questionnaire data source with a sample size of 100 samples. Data analysis uses Moderated Regression Analysis (MRA). The research results obtained a constant value of 2.078 indicating customer satisfaction before being influenced by the webform variable. Then the regression coefficient value of 0.532 The results of the t-test obtained a t-sig value < Î±5% (0.05), namely 0.000 < 0.05 and it can be stated that web form has a significant effect on customer satisfaction. The MRA test results show that knowledge is a quasi-moderator or pseudo-moderator variable between the dependent variable customer satisfaction and the independent variable webform.